Thelma & Louise - Scott, Ridley; Khouri, Callie; Sarandon, Susan, 1946-; Davis, Geena; Keitel, Harvey; Zimmer, Hans.; Star Partners III, Ltd.; MGM Home Entertainment Inc. (Santa Monica, CA : MGM Home Entertainment, 2003)
A waitress and a housewife try to get away from their boyfriend and husband for a weekend but instead end up on a crosscountry crime spree.
Originally released as a motion picture in 1991.
Features: documentaries, audio commentary, deleted scenes, alternate ending, multi-angle storyboards, music video.
Director of photography, Adrian Biddle; production design, Norris Spencer; film editor, Thom Noble; music, Hans Zimmer.
Susan Sarandon, Geena Davis, Harvey Keitel, Brad Pitt, Timothy Carhart, Michael Madsen.
MPAA rating: R.
DVD, Dolby digital, 5.1 surround.
Keywords: Fugitives from justice -- Drama; Action and adventure films; Action and adventure films; Fugitives from justice; Drama